DISTINCTION BETWEEN PENAEUS INDICUS H. MILNE EDWARDS AND PENAEUS MERGUIENSIS DE MAN (CR USTACEA : PENAEIDAE) WITH SPECIAL REFERENCE TO JUVENILES - Muthu, M S; Rao, G Sudhakara (Indian Journal of Fisheries, 2011)
Clear-cut differences between the juveniles of PCllaellS illdiclIs and Pellaellsmerglliâ‚¬lIsis are pointed out in this paper. On the basis of the . colour pattcrn of theantcnnal flagella, antennular flagella and the pJeopods, and the disposition of therostral teeth it is nOw possible to identify the juveniles of P. illdiclis and P.lIlerglliellsiswith certainty.